GAS IN PLACE PREDICTION OF COAL BED METHANE EXPLORATION WITH PROXIMATE DATA, PIT “HMG”, WEST BANKO, SOUTH SUMATRA - GANI, REZA MOHAMMAD GANJAR; Arbi, Hafsanjani; Firmansyah, Yusi; Nurdrajat, .; Alfadli, Muhammad Kurniawan (Fakultas Teknik Geologi Universitas Padjadjaran, 2018)
The energy demand are increase everyday, but the supply insufficiently if only depends on conventional energy. Coal bed methane exploration are one of the unconventional energy that can fulfill energy demand. The main aspect of coal bed methane exploration are the reserve of gas in place. In this research are use conventional data to approach a prediction and calculation of gas in place at PIT “HMG”, West Banko, Tanjung Enim, South Sumatra. Based on the analysis shows that the gas content are increase as the deeper of seam, and the total gas in place are 235.30 MMcf, with Seam C has the highest value 72.47 MMcf.